QTL mapping of resistance to late leaf spot in groundnut (Arachis hypogaea L.) - Cuc, Luu Minh; Quang, Vu Duc (Academia Journal of Biology, 2014)
Cultivated groundnut (Arachis hypogaea L.) is an important oilseed crop grown extensively throughout the semi-arid tropics of Asia, Africa and Latin America. Late leaf spot (LLS) caused by Phaeoisariopsis personata is one of the major diseases significantly decreasing in groundnut yields. This study aimed to construct a linkage map as well as a map for QTLs conferring resistance to late leaf spot in groundnut. Parental polymorphism survey of the two lines of ICG99001 (LLS-resistant) and TMV2 (LLS-susceptible) showed that 85 out of 363 SSR markers used were polymorphic for the 2 parental lines. A population of 178 F2 plants from the cross of ICG99001xTMV2 was used to construct a linkage map. A map of 15 linkage groups with 81 SSR markers was built. The total length of the map was 1475.4 cM with the average distance between two markers being 18.4 cM. The traits LF3 (lesion frequence per cm2 of leaf), LC3 (lesion number per leaf) and LAD5 (leaf area of damage) were used for QTL analysis and mapping. It showed that these three traits appeared to be controlled by 8 QTLs that located on the linkage groups 2, 3, 4, 6, 7 and 8. The two QTLs namely Qlf2 and Qlf7 explained 32.7% of the total phenotypic variation for the LF3 trait, while the three QTLs such as Qlc4, Qlc7 and Qlc8 explained 40.3% of the total phenotypic variation for the LC3 trait, and the other three QTLs such as Qlad3, Qlad6 and Qlad8 explained 31.2% of the total phenotypic variation for the LAD5 trait. A possibility for practical utilization of the SSR markers closely located to the QTLs was discussed.